In vitro penetration of alpha arbutin niosome span 60 system in gel preparation - Desnita, Rise; Luliana, Sri; Anggraini, Silvana (Pharmaciana, 2017)
Alpha arbutin is a hydrophilic compound which is difficult to pass trough the stratum corneum. One of the effort to increase the penetration of the drug through the stratum corneum is by making in niosome system. This study aims to determine the optimum concentration of span 60 to improve the entrapment efficiency of niosome and investigate the increasing penetration of alpha arbutin using the niosome system in the preparation of the gel in vitro. Niosome consist a mixture of span 60 and cholesterol it made by thin layer hydration method. Concentration of span 60 was varied into three formulas were 100, 150 and 200 µmoL. The formulation of gel was made in two formulas including formulation of niosome alpha arbutin and alpha arbutin in gel. The determination of enterapment efficiency showed that formula 100µmol has an optimum enterapment efficiency by 99.09%±0.1. The in vitro penetration tests with shed snake skin membrane showed that usage span 60 as a niosome composer could increase penetration of alpha arbutin in gel formulation with cumulative numbers of diffusion in 8 hours was 91.62%±2.32 compared to alpha arbutin in gel without niosome system about 73.00%±0.94.7.